Development of Problem Based Learning (PBL) Method Based on Local Wisdom in Institutional Accounting Practicum Subject - Valentina, Angger Aji Dwi; Joko Widodo, Joko Widodo; Kusumantoro, Kusumantoro (Universitas Negeri Semarang, 2024)
This research was conducted to address challenges in enhancing students' critical thinking skills at SMK Muhammadiyah 1 Semarang through the development of Problem Based Learning (PBL) method based on local wisdom in the Institutional Accounting Practicum subject. The development method follows Thiagarajan and Semmel's (1974) model with a 4-D development approach, starting from module design to validation by experts and field trials. The aim of this research is to describe the development of PBL method based on local wisdom to improve students' critical thinking skills, and to analyze the validity and effectiveness of the method. The research method uses constructivism theory, focusing on student interaction with the learning environment. The results show that the PBL method based on local wisdom effectively improves students' critical thinking skills. Module validation indicates an excellent category, while field trials received positive responses from students. The improvement in students' critical thinking skills is evidenced by a high N-Gain value, reaching 0.567. These findings suggest that the PBL method based on local wisdom can be recommended as an effective learning approach for the Institutional Accounting Practicum subject at SMK Muhammadiyah 1 Semarang.